Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Net Profit Margin (NPM) Pada PT Unilever Indonesia Tbk Periode 2014-2023 - Widyanti, Mila; Intan Sari, Widya (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of cash turnover and accounts receivable turnover on Net Profit Margin (NPM) at PT Unilever Indonesia Tbk during the period 2014-2023. The method used is a quantitative method with an associative approach, where the data analyzed is secondary data in the form of the company's annual financial statements accessed through the company's official website, www.unilever.co.id. and the data used is financial statement data for 10 years from 2014 - 2023. The data analysis technique uses multiple linear regression tests tested using SPSS version 24. The results showed that first, Cash Turnover does not have a significant partial effect on Net Profit Margin (NPM), with a significance value (Sig.) of 0.300 > 0.05. Second, Accounts Receivable Turnover also does not have a significant partial effect on Net Profit Margin (NPM), with a significance value of 0.712 > 0.05. Third, based on the simultaneous test results, Cash Turnover and Accounts Receivable Turnover do not have a significant simultaneous effect on Net Profit Margin (NPM), with a significance value of 0.417 > 0.05. The results of the Coefficient of Determination test show that the influence of Cash Turnover and Accounts Receivable Turnover is 0.221, meaning that the percentage contribution of the independent variables (Cash Turnover and Accounts Receivable Turnover) to Net Profit Margin (NPM) is 22.1%, while the remaining 77.9% is influenced by other variables not examined in this study.